Gestational administration of aqueous leaf extract of Jatropha tanjorensis alleviated postpartum emotional and cognitive dysfunction in rats (Wistar strain) (Nigerian Journal of Physiological Sciences, 2023)
This study examines the effect of gestational administration of aqueous leaf extract of Jatropha tanjorensis (JT) on postpartum-like behavioural outcomes to delineate its possibility as a prophylactic, therapeutic agent in the treatment of postpartum symptoms. Inseminated female rats (120-150g) were grouped into two-control and JT group (n=10). Control received 20 ml/kg of distilled water and JT group received 500 mg/kg of JT orally once daily for 21 days in gestation. Non-pregnant rats were excluded from the study. Parameters assessed at postpartum include antidepressant-like (force swim test, FST; tail suspension-test, TST), locomotor (open field test, OFT), anxiolytic-like (elevated plus maze, EPM; light-dark box, LDB), learning and memory (T-maze; novel object recognition task, NORT), social (nest score) and analgesic-like (hot plate test, HPT; tail flick test, TFT) behaviours. JT increased (P